Analisis Karakteristik Kecelakaan Lalu Lintas pada Ruas Jalan Nasional Nagari Sungai Lansek Kabupaten Sijunjung dengan Menggunakan Metode Angka Ekivalen Kecelakaan (AEK) dan Teknik Korelasi - Roza, Angelalia; Wahab, Wilton; Haryati, Novy; Muchlian, Meli; Fori, Alfanda Trizia (Jurnal Ilmiah Rekayasa Sipil, 2024)
The national road through Nagari Sungai Lansek, Sijunjung district (3 km long with an effective width of 7 meters) has a relatively high accident frequency where the total traffic accidents in the 2020-2022 range are always increasing. The aim of this research is to identify the factors that contribute to accidents at the research location. Specifically, the research locations are divided into three areas, namely Jorong Cilacap, Jorong Sikayan, and Jorong Sungai Ampang. The characteristics of the accidents observed are the type of accident, time of the accident, type of vehicle, and location of the accident. The analytical approach used in this research is the AEK (Accident Equivalent Analysis) method and correlation techniques. Based on the time of occurrence, the most diverse accidents were found between 06.00-19.00 with a total of 20 cases. Based on the type of vehicle most frequently involved in accidents, data was obtained on private cars and trucks for 17 cases. The type of accident that occurred most frequently was frontal collision with 11 cases. Based on the geographical context of the incident, a total of 11 incidents were observed in the Sungai Ampang area where driver factors contributed to a total of 17 incidents. The age range of drivers involved in accidents ranges from 16-30 years. Efforts to mitigate traffic accidents in the research area include implementing traffic education initiatives as well as implementing strict sanctions for road users who violate traffic regulations. Providing education regarding correct driving techniques and etiquette in traffic, as well as understanding the importance of traffic signs needs to be carried out in line with the provision of signs and improving road lighting at the study location.